Development of attachment for customized steering rack on one seater drag buggy - Muhammad, Shahrin Suhaimi (2008)
The title for this project is Development of Attachment for Customized Steering Rack on One Seater Drag Buggy. This project is under the UMP Mechanical Faculty. The main target for this project to the final year project student is to design, fabricate and analysis the customized mechanical part at the steering system of this buggy. This is to achieve the objective which is the steering system for the buggy is function without any problem. The steering system is very important to a vehicle to control and to navigate the vehicle movement direction. The system used mechanical principle to transfer the rotation from the steering wheel to the wheel through the steer rack that consist mechanical part such as pinion gear, bar gear and shaft. The analysis of the part is very important to gain the information on the maximum stress, minimum stress, load, FOS and the application of each material used to withstand the load. This buggy is design to roll at extreme terrain such as off-road and mud. The fabrication of the customized part and attachment of the part must be done properly to withstand the environment used of this vehicle. The other important aspect during fabrication and attachment process is the driver safety, this aspect is the priority during the development of the system